Pioneer Rocketry- 1st Place Midwest Rocket Launch 2017 - Guither, Adrian; Dickler, Jane; Oberhauser, Grant (Proceedings of the Wisconsin Space Conference, 2018)
The Midwest High Power Rocket Launch Competition is hosted by the Minnesota Space Grant Consortium every year. This year the competition was to design and build an â€œadaptableâ€ rocket that was able to fly on very different high power rocket motors to the same altitude. While some teams attempted to achieve this goal with air brakes or via adding additional mass to the rocket, we chose to utilize passive aerodynamic forces in our design. We are very proud that we were able to win first place in this competition. While we did not achieve the highest flight score, we were very close to the maximum value achieved by any team. We are especially proud of how well our fully passive design worked, reaching apogees of 6211 ft on the aerotech J90, and 6220 ft on the cesaroni K2045, a difference of only 9 ft.